Dietary Supplementation With Fish Oil Enhances the Growth and Reproductive Performance of Female Broodstock Haliotis discus hannai - Weiguang Zou; Jiacheng Gan; Yanbo Liu; Yawei Shen; Jiawei Hong; Yaobin Ma; Chunxiang Ai; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture Nutrition)
Macroalgae have long been utilized as a natural feed source in abalone aquaculture. The switch to formulated feeds improves nutritional control while reducing the cost instability of natural feeds. Recently, lipid supplementation has received a lot of attention since it is essential to the early developmental and broodstock stages of aquatic species. The present study aimed to investigate how the growth and reproductive performances of female broodstock Haliotis discus hannai were affected by the dietary supplementation of five lipids: fish oil (FO), perilla seed oil (PO), safflower oil (SO), olive oil (OO), and lard (LO). A total of 500 adult female abalones were randomly divided into five groups (four replicates per group) and fed with five lipid-supplemented diets for 90 days. The LO group was the worst (p<0.05), while the FO group significantly showed the best growth performance, gonad index (GI), fertility, fertilization rate, larvae hatching rate, and larval attachment rate (p<0.05). Meanwhile, the FO and PO groups exhibited significantly higher levels of very low-density lipoprotein (VLDL), vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), progesterone (PROG), and 17β-estradiol (E2) than the LO group (p<0.05), indicating their higher ovarian developmental maturity. Furthermore, histological and fatty acid analysis revealed that the FO group contained high levels of polyunsaturated fatty acids such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which may contribute to ovarian maturation and egg quality. Therefore, the best lipids for improving the growth and reproductive performances of female abalone might be FO enriched in highly unsaturated fatty acids rather than plant-derived lipids, providing new insights into nutritional research and applications in vegetarian mollusks.